Toxikologische Prüfung – Mythen und Fakten - Robert Hess (CHIMIA)
Toxicology provides the basic mechanism to evaluate the health hazards of chemicals to which man is exposed purposely or unknowingly to significant levels. Implicit is the role of toxicology in defining the limits and conditions of the safe use of chemical products. It is assumed that reliable experimental procedures are available to arrive at a definition of the probable risk and its magnitude. The evaluative and predictive process always relates to the biological effects observed, the nature of which may differ considerably between the various types of toxicity studies. It follows that a meaningful safety assessment necessitates the understanding of the interpretative value of the data on which it is based.